Pengaruh Gaya Kepemimpinan Terhadap Kepuasan Kerja Pengurus Koperasi Unit Desa di Kabupaten Barito Kuala - Astuti, Dita Dhea; Hasanah, Mahmudah; Ratumbuysang, Monry Fraick Nicky Gillian; Nor, Baseran (Universitas Negeri Surabaya, 2024)
This research aims to determine the effect of leadership style on job satisfaction of village unit cooperative administrators in Barito Kuala district. The population used in this research were all village unit cooperative administrators, namely 37 people from 10 village unit cooperatives in Barito Kuala Regency. This research uses quantitative research, with descriptive analysis type. Data collection techniques use questionnaires, interviews and observation. The data analysis technique used SPSS Statictics version 25. The results of the study found that the leadership style variable had a positive effect on job satisfaction of village unit cooperative administrators in Barito Kuala Regency.